Epidemiological and genetic analysis of Cetacean Morbillivirus circulating on the Italian coast between 2018 and 2021 - Vargas-Castro, Ignacio; Peletto, Simone; Mattioda, Virginia; Goria, Maria; Serracca, Laura; Varello, Katia; Sánchez-Vizcaíno, José Manuel; Puleio, Roberto; Nocera, Fabio Di; Lucifora, Giuseppe; Acutis, Pierluigi; Casalone, Cristina; et al. (Frontiers in Veterinary Science, 2023)
Cetacean Morbillivirus has caused several outbreaks, unusual mortality events, and interepidemic single-lethal disease episodes in the Mediterranean Sea. From 2012 a new strain with a northeast (NE) Atlantic origin has been circulating among the Mediterranean cetaceans, causing numerous deaths.The objective of this study was to determine the prevalence of CeMV in cetaceans stranded in Italy between 2018 and 2021, and to characterize the strain of CeMV circulating.Out of 354 stranded cetaceans along the Italian coastlines, 113 resulted CeMV-positive. This prevalence (31.9%) is one of the highest reported without an associated outbreak.All marine sectors along the Italian coastlines, except for the northern Adriatic coast, reported a positive molecular diagnosis of CeMV. In one third of the CeMV positive cetaceans submitted to histological evaluation, a chronic form of the infection (detectable viral antigen, absence of associated lesions and concomitant coinfections) was suspected. Tissues from 24 animals were used to characterize the strain, obtaining 57 sequences from phosphoprotein, nucleocapsid, and fusion protein genes, which were submitted to GenBank. Our sequences showed the highest identity with NE-Atlantic strain sequences, and in the phylogenetic study, they clustered together with them. Regarding age and species, most of these individuals were adults (17/24, 70.83%) and striped dolphins (19/24, 79.16%).